"Who you know affects what you know": Knowledge transfer in the university–private partnership – a social capital perspective. Issue 4 (August 2022) - Hakami, Maram; Pradhan, Sojen; Mastio, Emmanuel
The research literature on university–private partnerships shows that these partnerships can contribute significantly to the building of a knowledge-based economy. At the heart of this contribution is the practice of knowledge transfer. Through the analytical lens of social capital theory, this paper reports on a systematic review of 23 studies, from 2000 to 2021, on partnerships between universities and private sector organisations. The findings reveal inconsistencies in knowledge transfer, especially from the perspective of the cognitive frame of this theory. Based on these findings, a more rigorous theoretical framework is proposed for the enhancement of knowledge transfer in such partnerships, as moderated by the intermediary factor, and future research directions are suggested.